Distal tephras along the SE European margin date powerful explosive eruptions from the Elbrus volcanic center (Greater Caucasus). (15th January 2023) - Ponomareva, Vera; Portnyagin, Maxim; Danišík, Martin; Konstantinov, Evgeny; Zelenin, Egor; Tkach, Nikolai; Hauff, Folkmar; Schmitt, Axel K.; Friedrichs, Bjarne; Romanyuk, Boris; Guillong, Marcel; Kirkland, Christopher L.; et al.
Abstract: Knowledge of temporal patterns of past explosive eruptions is necessary to understand possible future eruptive behavior. However, volcanic records based on geological reconstructions remain incomplete. This inference is true not only for remote and sparsely populated areas like the Aleutian or Kurile-Kamchatka arcs, but also for Europe, where past large explosive events are continuously recognized in the geological record. Here we report the first age and geochemical data on the violent middle to late Pleistocene explosive eruptions from the Elbrus volcanic center (Greater Caucasus), which towers over the densely populated regions in southern Russia and Georgia. We attribute six disparate ash deposits found in the terrestrial and marine sediments along the SE European margin to the Elbrus volcanic center based on major and trace element compositions of individual shards of volcanic glass and radiogenic Sr-Nd-Pb isotope compositions of bulk tephra. We suggest that these deposits represent products of five different eruptions that were dispersed over distances of more than 150–560 km from their source. Three of four eruptions are dated at 522 ± 36, 258 ± 13, and 84.6 ± 7.4 ka by a combined zircon U–Th–Pb and (U–Th)/He approach. One sample revealed an overdispersed spectrum of single crystal (U–Th)/He dates with an average of 176 ± 40 ka. Zircon characteristics and statistical deconvolution of the geochronology data suggest that this sample contains zircon crystals from two different eruptions tentatively dated at 156.5 ± 7.7 ka and 222.8 ± 13 ka. These eruption ages represent the first recognition of a suite of large pumiceous eruptions from the Elbrus volcanic center postdating the previously known explosive activity, documented by ∼800 ka old welded tuffs. These data also provide the first geochemical and geochronological characterization of both proximal and distal Elbrus tephra glasses and contribute to the global tephra database, permitting the identification of Elbrus tephras in distal terrestrial and marine paleoenvironmental archives and hence their use as paleoclimate and archaeological markers. We consider the significance of the identified tephras for paleoenvironmental research and show their potential for tephrochronological studies in the East European Plain and adjacent areas. Highlights: First age and geochemical data on tephra from the Elbrus volcanic center (Caucasus). Four large silicic explosive eruptions from Elbrus identified between 500 and 85 ka. Elbrus tephra deposits found at distances of 150–560 km from the source. Dated Elbrus tephras may serve as markers for paleoenvironmental research.